Attachement Needs And Social Networking Sites - Özad, Bahire Efe; Uygarer, Gülen (SOC PERSONALITY RES INC, 2014)
Attachment is a significant human need throughout life. Recent developments in communication technologies indicate that social networking sites (SNS) play a significant role in forming relationships. In addition to forming real-life relationships, students also form new relationships and maintain already existing relationships through SNS. In other words, in line with uses and gratifications theory, new media are used to gratify students' needs. In this study conducted in 2011, the authors have compared real-life friendships with friendships formed through SNS, in fulfilling the attachment needs of students at the English Preparatory School at the Eastern Mediterranean University. They have found statistically significant differences between attachments formed in real life and those formed through SNS. Therefore, they determined that, SNS play a significant role in satisfying the need for attachment among young people who are at the outset of their tertiary education.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: attachment needs; social networking sites; communication; university students; uses and gratifications theory; social networking sites, PSYCHOLOGY; SOCIAL, attachment needs, communication, university students; PREDICTORS, uses and gratifications theory; Age, Social networks, Behavior; Gender, Higher education, Self esteem; Students, Families & family life, Social research